Development of an Interactive Picture Story E-book for Enhancing Early Childhood Sexual Knowledge - Sonita, Sandra; Utoyo, Setiyo; Rakimahwati, Rakimahwati; Nurhafizah, Nurhafizah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Because children have a limited level of sexual knowledge, teachers have not been able to use more diversified and effective technology-based learning materials to stimulate students. The purpose of this study is to evaluate the effectiveness of the interactive picture story e-book "Knowing Our Body Parts" in enhancing children's sexual literacy.  Using the ADDIE approach (Analyze, Design, Development, Implementation, Evaluation), this kind of research is development research. This study includes eight children from Group B, as well as three experts in learning media, content, and instruments. In this study, questionnaires, interviews, and observation were used as data gathering methods.  A questionnaire was employed as the research tool.  Both quantitative and qualitative descriptive analyses were used to examine the data.  The study's findings demonstrate that the process of developing the e-book "Knowing the Parts of Our Body"—which consists of illustrated stories—is successful in improving sexual knowledge.